Speech by Maria Laura Bergamaschi and Angelo Villa - February 4th, 2021 (Balthazar, 2022)
Transcription of Maria Laura Bergamaschi and Angelo Villa's speech during the cycle of conferences on Civil disobedience 2020-2021.
Keywords: subjectivity; analytic ethics